Daniel Kieffer : a derivà — Au gré de l’événement, sous la gouverne du sensible - Perraton, Charles (CV Photo)

(untitled) (Les Productions Ciel variable, 1996)
Daniel Kieffer's photographs constantly transport the viewer from one side of the lens to the other. With his camera at the service of sensation rather than the "beautiful image," Kieffer returns us to the essence of an art that teaches us about "the unconscious view" (Walter Benjamin). Seeing and experiencing sensation seem to be the conditions of artistic expression. The living soul is capable of anything. What can be expressed is made possible only under the guidance of sensation. Knowing things (learning) is not the only purpose of the art of seeing; this art also allows us to understand things and thus interpret the world better (become the other at the moment one encounters it). Through his witnessing, the photographer enables us to see the world from the outside (distance), but, through his involvement, he participates in what he witnesses (proximity); the result is a pragmatic, disturbing effect on our position with regard to the world and its representation. Excerpt of a text by Charles Perraton